EXPLORING STUDENTS’ ATTITUDES TOWARD ENGLISH ACCENTS AND THEIR AWARENESS OF THE VARIETIES OF ENGLISH - Inudom, Podjaman; Tongsukkaeng, Wilawan; Thathong, Supakhawat; Supakavanich, Wanuchida (Journal of MCU Nakhondhat, 2023)
The objectives of this research article were 1) to study the attitudes of students toward varieties of English accents and 2) to study the awareness of students towards varieties of English. A type of research used in this study was qualitative research. The population was undergraduate students from a university in the Northeast of Thailand. Eight students were selected by purposive random sampling. Data was analyzed by using the thematic analysis method. The instrument used to collect data was the semi-structured interview. The results of the research were shown as follows. 1) The attitudes of students toward various accents of English can be summarized into three points. 1.1) Firstly, the students had positive perspective and attitudes towards the variety of English accents. 1.2) Secondly, American English was considered as the best variation of the English language, especially pronunciation, that should be taught in English class. 1.3) Finally, the students did not show a significant awareness towards the varieties of the English language as they value communication over accents. 2) The students’ awareness of the varieties of the English language were divided into three points. 2.1) Firstly, British, American, Indian, Filipino, Thai, Singaporean, Canadian, French, Italian, and Chinese accents of English were recognized by the students. 2.2) Secondly, American, British, and Australian accents were preferred to be acquired the most by the students. 3.3) Finally, American and British accents were considered as the best two varieties of English accent.